Genome Characterization of a Novel Wastewater Bacteroides fragilis Bacteriophage (vB_BfrS_23) and its Host GB124 - Tariq, Mohammad A.; Newberry, Fiona; Haagmans, Rik; Booth, Catherine; Wileman, Tom; Hoyles, Lesley; Clokie, Martha R. J.; Ebdon, James; Carding, Simon R. (Frontiers in Microbiology, 2020)
Bacteroides spp. are part of the human intestinal microbiota but can under some circumstances become clinical pathogens. Phages are a potentially valuable therapeutic treatment option for many pathogens, but phage therapy for pathogenic Bacteroides spp. including Bacteroides fragilis is currently limited to three genome-sequenced phages. Here we describe the isolation from sewage wastewater and genome of a lytic phage, vB_BfrS_23, that infects and kills B. fragilis strain GB124. Transmission electron microscopy identified this phage as a member of the Siphoviridae family. The phage is stable when held at temperatures of 4 and 60°C for 1 h. It has a very narrow host range, only infecting one host from a panel of B. fragilis strains (n = 8). Whole-genome sequence analyses of vB_BfrS_23 determined it is double-stranded DNA phage and is circularly permuted, with a genome of 48,011 bp. The genome encodes 73 putative open reading frames. We also sequenced the host bacterium, B. fragilis GB124 (5.1 Mb), which has two plasmids of 43,923 and 4,138 bp. Although this phage is host specific, its isolation together with the detailed characterization of the host B. fragilis GB124 featured in this study represent a useful starting point from which to facilitate the future development of highly specific therapeutic agents. Furthermore, the phage could be a novel tool in determining water (and water reuse) treatment efficacy, and for identifying human fecal transmission pathways within contaminated environmental waters and foodstuffs.